Norepinephrine upregulates the expression of tyrosine hydroxylase and protects dopaminegic neurons against 6-hydrodopamine toxicity. (December 2019) - Zhu, Meng-Yang; Raza, Muhammad U.; Zhan, Yanqiang; Fan, Yan
Abstract: As a classic neurotransmitter in the brain, norepinephrine (NE) also is an important modulator to other neuronal systems. Using primary cultures from rat ventral mesencephalon (VM) and dopaminergic cell line MN9D, the present study examined the neuroprotective effects of NE and its effects on the expression of tyrosine hydroxylase (TH). The results showed that NE protected both VM cultures and MN9D cells against 6-hydroxydopamine-caused apoptosis, with possible involvement of adrenal receptors. In addition, treatment with NE upregulated TH protein levels in dose- and time-dependent manner. Further experiments to investigate the potential mechanisms underlying this NE-induced upregulation of TH demonstrated a marked increase in protein levels of the brain-derived neurotrophic factor (BDNF) and the phosphorylated extracellular signal-regulated protein kinase 1 and 2 (pERK1/2) in VM cultures treated with NE. In MN9D cells, a significantly increase of TH and pERK1/2 protein levels were observed after their transfection with BDNF cDNA or exposure to BDNF peptides. Treatment of VM cultures with K252a, an antagonist of the tropomyosin-related kinase B, blocked the upregulatory effects of NE on TH, BDNF and pERK1/2. Administration of MEK1 & MEK2 inhibitors also reversed NE-induced upregulation of TH and pERK1/2. Moreover, ChIP assay showed that treatment with NE or BDNF increased H4 acetylation in the TH promoter. These results suggest that the neuroprotection and modulation of NE on dopaminergic neurons are mediated via BDNF and MAPK/ERK pathways, as well as through epigenetic histone modification, which may have implications for the improvement of therapeutic strategies for Parkinson's disease. Highlights: NE protected both VM cultures and MN9D cells against neurotoxicity. NE upregulated protein levels of TH and BDNF. Both NE and BDNF increased expression of pERK1/2. Effects of NE and BDNF are mediated by TrkB and MAPK pathway. H4 acetylation may be involved in effects of NE and BDNF.